USE OF DIFFERENT DOSES OF OVAPRIM TO INDUCED SIGNAL BARB (Labeobarbus festivus, Heckel 1843) - Alfredo Manik; Netti Aryani; Hamdan Alawi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted from April to November 2015. The aim of this research was to determine the effect of ovaprim doses on spawning success of signal barb (Labeobarbus festivus, Heckel 1843). The method used in this research was an experimental method with Completely Randomized Design (CRD) with one factor, four treatments and three replications. The treatment used in this research was an injection of ovaprim with different doses i.e : P0 (0,2 mL NaCl physiology 0,9 %/kg of body weight), P1 (0,5 mL/kg of body weight), P2 (0,7 mL/kg of body weight) and P3 (0,9 mL/kg of body weight). The results showed that ovaprim dose of 0,7 mL/kg of body weight was the best in turn of latency time (5.32 hours), total eggs stripping (14.095 eggs/g gonads), egg diameter (0,91 mm), egg maturity (87,7 %), Ovi Somatic Index (20,15 %), fertility rate (40,39 %), hatching rate (14,85 %), and survival rate (38,07 %).Key words : Ovaprim, Spawning, Signal Barb (Labeobarbusfestivus, Heckel 1843)